International Implementation of a PROficiency based StePwise Endovascular Curricular Training (PROSPECT) in Daily Practice. (December 2021) - Soenens, Gilles; Lawaetz, Jonathan; Bamelis, Anne-Sophie; Nayahangan, Leizl J.; Konge, Lars; Eiberg, Jonas; Van Herzeele, Isabelle
Abstract : Objective: A randomised controlled trial (RCT) showed superior real life endovascular performance of trainees after PROficiency based StePwise Endovascular Curricular Training (PROSPECT) compared with traditional training. This study aimed to determine whether PROSPECT can be implemented routinely in surgical training (registry) and to identify the associated effects, facilitators, and barriers to implementation. Methods: This was a multicentre prospective registry to evaluate real life PROSPECT implementation effects. Cognitive ability was tested with a Multiple Choice Question test (MCQ) (max. score 20 points), while technical skills were assessed with a Global Rating Scale (GRS) (max. score 55 points), Examiner's Checklist (max, score 85 points), and simulator metrics. A cross sectional anonymous survey for both trainees and faculty evaluated the programme's implementation. Results: The PROSPECT registry was implemented in five centres in four countries over a period of three years. Only 17 of 48 starting trainees completed PROSPECT, resulting in a dropout rate of 65%. Participants who completed the programme showed significant improvement in the GRS (median 26 vs. 44, p  = .018) and Examiner's Checklist (median 53.5 vs. 80, p  = .028) after the programme. The survey was completed by 13/17 faculty members (76%) and 38/57 trainees who participated either in the initial PROSPECT RCT or the registry (67%). PROSPECT was perceived to provide more endovascular training opportunities, but non-availability of logistical/technical support, lack of training time within the working schedule, and little trainee motivation hindered broad implementation. Conclusion: PROSPECT has a significant effect on performance, and trainees and faculty agree that PROSPECT is a valuable addition to surgical training. However, external and internal factors pose significant barriers to integration of this simulation based programme into daily practice leading to a high dropout rate. To integrate PROSPECT into contemporary surgical training, it should be a prerequisite to treating real patients and protected training time should be provided, combined with accessible support.